Circulating micronutrients levels and their association with the risk of endometriosis - Zhang, Yanna; Li, Meng; Zhang, Feifei; Lin, Jiaoya; Yuan, Hong; Nian, Qing (Frontiers in Nutrition, 2024)
Background: Endometriosis, a prevalent gynecological disease, has an unclear pathogenesis. Micronutrients play a crucial role in disease development, which has led to an investigation of their association with endometriosis.In this study, we analyzed the relationship between 15 micronutrients and endometriosis using both univariate and multivariate Mendelian randomization (MR) to assess the correlation. The results were validated using high-performance liquid chromatography (HPLC).The univariate MR analysis indicated that vitamin B6 (OR=1.7060, 95% CI: 1.1796-2.4672, P=0.0045) and calcium (OR=1.4834, 95% CI: 1.0747-2.0475, P=0.0165) are associated with an increased risk of endometriosis. Higher intakes of vitamin B6 and calcium are associated with a greater likelihood of developing endometriosis. The MR Egger regression's intercept term demonstrated no evidence of pleiotropy(P>0.05) or heterogeneity (P>0.05) in the SNPs for calcium and vitamin B6. In multivariate MR analysis, vitamin B6 (OR=2.397, 95% CI: 1.231-4.669, P=0.01) was linked to an increased risk of endometriosis, independently of other exposure factors. No significant heterogeneity (P=0.831) or pleiotropy (P=0.369) was observed in the genetic variation of endometriosis, affirming the reliability of the multivariate MR analysis. HPLC confirmed a significant increase in serum levels of vitamin B6 and calcium, aligning with the MR analysis findings.Conclusion：Vitamin B6 and calcium may be associated with this disease, with vitamin B6 potentially acting as an independent risk factor. Further research is essential to elucidate the role of micronutrients in disease, offering novel insights for prevention and treatment strategies.